Prevalence of Bacillus cereus on food handlers’ hands and in selected food sold at night market in northern Perak, Malaysia and its association with knowledge, attitude and practice of food handlers - Abdul Rahim, Noor Aniza (2021)
The night market is a prominent place for various types of delightful food. However, the lack of proper equipment can promote the growth of various pathogenic bacteria including Bacillus cereus because of uncontrolled storage temperature. This bacterium can be commonly found in rice, flour and starchybased food. The efficiency of food safety training that was taken by the food handlers can be observed by knowledge, attitudes, and practices (KAP) study. This research aimed to determine the prevalence of B. cereus in selected readyto- eat (RTE) food in the night market in northern Perak; to determine the antibacterial resistance profiles of the isolates to common antibiotics; and to identify the association between KAP level with the food handlers’ demographic characteristics and B. cereus hand carriage of the food handlers. Eighty-three RTE food and fifty-seven hands’ swab samples of food handlers were collected from twenty-five stalls at night markets in Kamunting, Taiping, and Bukit Merah, Perak. Both food and swab samples were tested for aerobic plate count and B. cereus identification. Positive isolates of B. cereus were further analyzed for antimicrobial susceptibility testing. KAP survey were conducted among food handlers after food and hands’ swab samples were collected. Data were analyzed using Minitab software to determine the prevalence of B. cereus and its association with the level of KAP among the food handler. Aerobic bacteria was detected from 89% of the food samples with a range of 102-106 CFU/g while 28% of them were contaminated with B. cereus with a range of 102-104 CFU/g. The percentage of B. cereus hand carriage detected was 42% from 57 respondents. B. cereus isolates detected from both food and hands’ swab samples showed resistance to tetracycline, chloramphenicol and clindamycin. The result from the KAP survey of the food handlers showed moderate scores for knowledge (74%) and high scores for attitude (92%) and practices (82%). Significant differences were reported in marital status (p-value: 0.000) and working experience (p-value: 0.001) towards handling practices. Furthermore, positive correlations were seen between attitude and practices score (pvalue: 0.000, r:0.681). On the other hand, the respondents' level of knowledge (p-value: 0.007) and practices (p-value: 0.006) were found to be significantly associated with B. cereus hand carriage whereas respondents with higher knowledge scores were found to be as B. cereus hand carriage. The findings concluded that a good knowledge score does not always portray the cleanliness of the food handlers. It is a call for authorities to emphasize food safety among food handlers especially at the night markets.